Essential components of schizophrenia care: a Delphi approach. - Fiander, M; Burns, T (1998)
Other than medication and access to in-patient care, there is little published consensus on the essential components of schizophrenia care. This paper reports a Delphi approach to the identification of these components. This approach identifies and measures the degree of consensus, using a structured iterative series of questionnaires by a group of experienced UK and Irish psychiatrists (n = 15) on the essential components. Pharmacotherapy, in-patient care and community mental health team (CMHT) staffing were explicitly excluded from the study. In total, 106 components were identified and their importance was rated twice. There was consensus on 92% of the components and strong consensus on 64%. The Delphi results were refined by the participants to produce 10 essential components of care.